2018
DOI: 10.1186/s12905-018-0527-y
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual hygiene management among women and adolescent girls in the aftermath of the earthquake in Nepal

Abstract: BackgroundMenstrual hygiene management (MHM) is an essential aspect of hygiene for women and adolescent girls between menarche and menopause. Despite being an important issue concerning women and girls in the menstruating age group MHM is often overlooked in post-disaster responses. Further, there is limited evidence of menstrual hygiene management in humanitarian settings. This study aims to describe the experiences and perceptions of women and adolescent girls on menstrual hygiene management in post-earthqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 27 publications
2
80
2
1
Order By: Relevance
“…Sanitation facilities were commonly cited to not be safe, clean, and accessible (Kwiringira et al, 2014;Sato et al, 2016;Khan et al, 2017;Aluko et al, 2018;Angoua et al, 2018;Dendup et al, 2018;Desalegn et al, 2018;Njuguna, 2019;Winter et al, 2019). Basic needs, such as soap and washing facilities, and hygienic products, such as toothpaste were documented as hygiene barriers (Budhathoki et al, 2018;Lubon et al, 2018). Moreover, women and girls often cited that critical challenges No 22.7% of students possessed genito-urinal schistosomiasis.…”
Section: Women Face Unique Wash and Mhm Challengesmentioning
confidence: 99%
See 4 more Smart Citations
“…Sanitation facilities were commonly cited to not be safe, clean, and accessible (Kwiringira et al, 2014;Sato et al, 2016;Khan et al, 2017;Aluko et al, 2018;Angoua et al, 2018;Dendup et al, 2018;Desalegn et al, 2018;Njuguna, 2019;Winter et al, 2019). Basic needs, such as soap and washing facilities, and hygienic products, such as toothpaste were documented as hygiene barriers (Budhathoki et al, 2018;Lubon et al, 2018). Moreover, women and girls often cited that critical challenges No 22.7% of students possessed genito-urinal schistosomiasis.…”
Section: Women Face Unique Wash and Mhm Challengesmentioning
confidence: 99%
“…A small fraction (6%) of studies focused on the role of MHM, where women reported a lack of proper MHM products, such as clean pads, in addition to private areas and an absence of water provisioning for cleaning and sanitation needs (Khan et al, 2017;Budhathoki et al, 2018;Davis et al, 2018). Davis et al (2018) demonstrated how one in 10 students missed school due to menstruation, and this could, in part be attributed to menstrual stigma.…”
Section: (Continued)mentioning
confidence: 99%
See 3 more Smart Citations